University of the Third Age and Computer literacy - Hnilička, Jakub; Horný, Stanislav, 1955-; Vilím, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2008)
Computer literacy has recently emerged as a new topic, complementing traditional literacy. While this issue affects every one of us, it is particularly important for people of post-productive age, who have not been able to become acquainted with information technology during their professional life. The National Computer Literacy Program provided a great opportunity to eliminate this illiteracy; unfortunately it came to an end together with termination of the Ministry of Informatics of the Czech Republic. It is striking that the State has been preparing projects in the area of e-Government, electronic census and electronic elections without having any developmental strategy for users of these ambitious projects. An opportunity to improve personal skills after the end of a professional career is provided by the University of the Third Age at the University of Economics, where students learn to use not only computers, but also the multimedia in the Graphic and Multimedia Laboratory. Unfortunately, this university is not accessible to everyone. The limitations consist particularly in the precondition of completed secondary education, but also in the available capacity. Thus, an option that is really available to everyone lies in the commercial sector, which offers a wide range of courses. These courses are provided either by software companies or by the ECDL (European Computer Driving License).
Vedoucí práce: Stanislav Horný
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2008
Rok obhajoby 2008
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses